The Impact of Family Environment, Self-Leadership, and Entrepreneurship Education on Entrepreneurial Interest of Mechanical Engineering Students - Nensy Aryasandy; Asmar Yulastri; Ganefri Ganefri; Nizwardi Jalinus; Jonni Mardizal (Jurnal Kewirausahaan dan Bisnis, 2024)
The purpose of the study to investigate the impact of family environment, self-leadership quality, and entrepreneurship education on the entrepreneurial interest of mechanical engineering students at Universitas Negeri Padang. Data was collected through questionnaires distributed to 96 mechanical engineering students at UNP who have participated in entrepreneurship subjects. The relationship between the independent variables and entrepreneurial interest was analyzed using regression analysis. The results revealed a strong and statistically significant positive relationship between the home environment and interest in entrepreneurship, explaining 35.5% of the variation, with a p-value of 0.000. Similarly, self-leadership exhibited a positive impact of 47.1% on entrepreneurial interest with a significance value of 0.000. Additionally, entrepreneurship education showed a significant and positive effect of 25.4% on entrepreneurial interest among UNP mechanical engineering students, with a significance value of 0.000. These findings are valuable for understanding the factors influencing entrepreneurial interest among mechanical engineering students at UNP. It can be used to enhance the entrepreneurship education and preparation programs at UNP and provide better support for students aspiring to become entrepreneurs.Keywords: active participation; emotional support; entrepreneurial interest; practical experience; student motivation